Sound studies of the architectural environment: urban soundscape and sound semantics - Troshkina, Olena; Troshkin, Arsenii; Gnatiuk, Liliia; Shevchenko, Liudmyla; Novoselchuk, Natalia (Landscape Architecture and Art, 2025)
The article is dedicated to a new field for Ukraine – the acoustic study of the architectural environment, the semantics of sound, and the impact of sound signals on human behavior in urban spaces. The concept of the soundscape, introduced into scientific discourse in the 1970s by R. Murray Schafer and his followers, is explored. They laid the foundation for and initiated acoustic studies of cities in the context of their auditory pollution. The methodology for studying the urban soundscape developed by them became the basis for contemporary practical work and was tested by students of the National Academy of Fine Arts and Architecture (Kyiv, Ukraine). Their task involved recording changes in the soundscape according to different types of urban spaces and observing human behavior under the influence of sound signals. All research results were visualized on graphic sound maps. The role of sound in perceiving the architectural space of a city is defined in comparison to the significance of sound in cinema. It is noted that, as in cinema, sound in the urban architectural environment has its own functions: illustration; contrast or counterpoint to the visual sequence; communication; synchronization; structuralization. As in films, sounds can emphasize events (e.g., the sound of a theatrical celebration in a city square), maintain tension in transitional spaces (e.g., the sound of a traffic light), warn of danger, obstacles, or threats (e.g., the sound of a siren), act as a dominant element indicating direction (e.g., a clock on a town hall), convey the novelty of a space or its mystery (e.g., unclear, atypical sounds for a given soundscape), and so on. Based on this, it is hypothesized that the architectural environment can be modeled by programming impressions of its perception and influencing people’s behavior within it. Sound is one of the most powerful tools for shaping the perception of architectural space, and sound compositions become an essential component of the sound environment of a modern city, requiring further research and the development of principles for urban sound design. The authors note that the study of the semantics of sound in general and sound signals in particular, as well as their influence on human behavior, is not yet complete but holds great promise for further development of such research on the architectural environment of cities, particularly in Ukraine.